PENGEMBANGAN MODUL ZAT ADITIF MAKANAN BERBASIS KEARIFAN LOKAL MASYARAKAT DESA RASAU JAYA UMUM - Andriyani, Putri; Masriani, Masriani; Muharini, Rini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to collect data of plants used as food additives by local people in Rasau Jaya Umum Village Kubu Raya Regency West Kalimantan, determine the validity, and the response of students of the modules developed. The form of study was Research and Development R&D. The source of this research data was local people in Rasau Jaya Umum and the students of class VIII of Kubu Raya Regency. Data were obtained by using observation sheets, module validity assessment sheets, and questionnaire responses of students to the module. The results showed that there are 18 species of 15 plant families used as natural additives, namely Liliaceae, Zingiberaceae, Amaranthaceae, Oxalidaceae, Rutaceae, Arecaceae, Poaceae, Gnetaceae, Malvaceae, Cactaceae, Pandanaceae, Piperaceae, Polygonaceae, Anacardiaceae, and Myrtaceae. Data about the plants then implemented into modules with content validity, presentation validity, linguistic validity, and graphic validity, each of which has a conten validityvalue of 1,00 with a valid category. The results of the initial phase trial of the module obtained the response of students with an average of 84,3% with very high criteria. The results of the field trial of the module obtained the response of students with an average of 86,1% with very high criteria.Â Keywords: Plants, Rasau Jaya Umum Village, Module, and Food Additives